Merjenje gibalne koordinacije pri športni vzgoji - Beranič, Lovro (Šport (Ljubljana), 2022)
A well-developed ability of motor coordination enables male and female students to perform movement in sports activities in a coherent and economical manner. Measurement of the ability to coordinate movement in students at school are based on knowledge of the biomechanical laws of movement and neuromuscular connections that condition its development. The motor ability of coordination in high school students aged 15 to 19 can be influenced by the development of basic motor skills, appropriately mastered motor technique of individual sports and motor tasks, where as the dominant ability of motor coordination we develop coordinated movement of upper and lower limbs, agility and rhythm. Measurement instruments for determining the ability to coordinate movement in students at school should be appropriate to their developmental characteristics, and should measure the dominant aspect of movement coordination, which is represented in the learning content of school physical education.
Keywords: dijaki; gibalne sposobnosti; meritve; šport; športna vzgoja; učenci